Wading pools, fading memories—place navigation in transgenic mouse models of Alzheimer's disease - Tanila, Heikki (Frontiers in Aging Neuroscience, 2012)
The Morris swim navigation task (‘water maze’) has been a primary research tools to assess hippocampal delpendent spatial learning and memory is rodents for three decades. Originally developed for rats, its application to mouse studies has been a tedious process, but nowadays there are more studies performed with the Morris swim task in mice than in rats. The task has proved to be particularly useful in demonstrating age-related memory impairment in transgenic mouse models of Alzheimer’s disease. This review focuses on task details that are most relevant for its application to mouse studies in general and characteristic patterns of impaired performance in Alzheimer model mice as compared with rodents sustaining hippocampal lesions.